Promiscuity and the evolutionary transition to complex societies. - Cornwallis, C; West, SA; Davis, K; Griffin, A (2010)
Theory predicts that the evolution of cooperative behaviour is favoured by low levels of promiscuity leading to high within-group relatedness. However, in vertebrates, cooperation often occurs between non-relatives and promiscuity rates are among the highest recorded. Here we resolve this apparent inconsistency with a phylogenetic analysis of 267 bird species, demonstrating that cooperative breeding is associated with low promiscuity; that in cooperative species, helping is more common when promiscuity is low; and that intermediate levels of promiscuity favour kin discrimination. Overall, these results suggest that promiscuity is a unifying feature across taxa in explaining transitions to and from cooperative societies.